METAFORA DAN IDEOLOGI FILM IKLAN MANDIRI SECURITAS - Handriyotopo, H.,; Lastoro, GR Lono; Gustami, SP (Institut Seni Indoensia Surakarta, 2018)
The Mandiri Securitas advertisement film is a corporate advertisement that contains a persuasive message to increase brand image as a leader in investment in the Stock Exchange or trusted banking investment in Indonesia. The metaphor in the Mandiri Securitas advertisement contains cinematographic images that borrow keris culture to be sided with banking culture. This qualitative descriptive study uses a semiotic approach to appropriate verbal and visual messages from the system of rhetorical marks